(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2019)
Nanostructured transition metal oxide nanoparticles possess a catalytic activity to hydrogen peroxide. Manganese dioxide particles are one of the promising and available modificators of the electrode surface. Nanostructured MnO2 deposited onto the surface of the electrode enhances the electron transport from the H2O2 molecule to the surface. Thus selectivity and sensitivity of H2O2 detection can be improved. There are a lot of different methods of the impregnation of manganese dioxide particles onto electrode surface. An electrophoretic deposition is one of the most simple and rapid. By adjusting the electrodeposition parameters, particles of different sizes or films can be obtained. A simple and novel hydrogen peroxide sensor based on layer-by-layer assembly of MnO2 nanoparticles and SiO2 film on the ITO electrode was developed. For this purpose MnO2 nanoparticles were electrodeposited on the surface of ITO electrode from MnSO4/CH3COOK solution. The electrochemical characteristics of the modified electrodes were investigated by cyclic voltammetry. The presence of MnO2 on the surface of modified electrode was indicated by the appearance of clear oxidation-reduction peaks of Mn(IV)/Mn(III,II) at E=0,65 V in the electrolyte solution in contrast to unmodified electrode. Optimization of measurement parameters such as the amount of MnO2, applied potential and pH value were studied in details. Under the optimum conditions, the calibration curve for H2O2 determination using modified electrode was linear in the range from 1×10−4 to 1×10−3 mol/dm3 with a detection limit of 0,09×10−4 mol/dm3 (S/N = 3). The linear rang for non-modified electrode was from 1×10−3 to 1×10−2 mol/dm3 with a detection limit of 1,8×10−4 mol/dm3 (S/N = 3). The modified ITO electrode was characterized by higher current than non modified ITO as a result of increasing of electroactive surface area and catalytic effect of electrodeposited MnO2. For the stabilization of MnO2 particles and protection of the electrode surface from impurities, the ITO/MnO2 was covered by thin silica film. The selectivity of H2O2 determination at ITO modified with MnO2/SiO2 was better than at ITO especially in the presence of ascorbic acid which is oxidized at the same potential as H2O2. The oxidation current of ascorbic acid was much higher than H2O2 at non-modified ITO in contrast to ITO modified with MnO2/SiO2. The developed ITO electrode modified with MnO2/SiO2 is a perspective element of amperometric sensor for the detection of hydrogen peroxide.